2012
DOI: 10.1177/1087057112452137
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of the Protein Methyltransferase SET7/9 Identified in a High-Throughput Screen

Abstract: Aberrant expression of chromatin-modifying enzymes (CMEs) is associated with a range of human diseases, including cancer. CMEs are now an important target area in drug discovery. Although the role that histone and protein (lysine) methyltransferases (PMTs) play in the regulation of transcription and cell growth is increasingly recognized, few smallmolecule inhibitors of this class of enzyme have been reported. Here we describe an assay suitable for primary compound screening for the identification of PMT inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Since both GATA1 and SET7 are overexpressed in breast cancer patients, and GATA1 and SET7 promote not only breast cancer cell growth but also tumor angiogenesis, inhibition of GATA1 and/or SET7 may be a useful strategy for breast cancer therapy. Recently, SET7 inhibitors have been identified [ 48 ]. It will be interesting to investigate whether these inhibitors repress cancer cell growth and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Since both GATA1 and SET7 are overexpressed in breast cancer patients, and GATA1 and SET7 promote not only breast cancer cell growth but also tumor angiogenesis, inhibition of GATA1 and/or SET7 may be a useful strategy for breast cancer therapy. Recently, SET7 inhibitors have been identified [ 48 ]. It will be interesting to investigate whether these inhibitors repress cancer cell growth and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Future xenograft assays are planned to further confirm our findings. Recently, several SET9 inhibitors with high potency and selectivity have been developed in high throughput screening assays [48]. However, the role of SET9 in disease pathways was poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…This clearly illustrates the context specificity of the SETD7 function. Moreover, there are several SETD7 inhibitors currently available [17][18][19][20][21][22][23] and some studies have suggested SETD7 inhibition as a potential anti-cancer therapy [20][21][22]. Therefore, there is a need to systematise current findings to identify the contexts that can lead to improvements in cancer diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%